Transmission Expansion Planning Including Reactive Power Procurement in Deregulated Environment - Singh, Kanwardeep; Padhy, Narayana Prasad; Sharma, Jaydev (Electric power components and systems, 2011)
This article proposes a novel approach for transmission expansion planning in pool-based deregulated electricity markets. The transmission expansion planning problem is formulated as an optimization problem consisting of minimization of annualized investment cost of prospective transmission lines and maximization of social welfare as an objective function, subject to operational and security constraints. Reactive power procurement cost to be paid to the generator companies, in addition to commonly used real power generation cost of generator companies and benefits of distribution companies/bulk consumers, have also been considered in the social welfare function. The reactive power procurement cost needs to be included in the social welfare function in order to pay compensation to generator companies for their reactive power supply in a deregulated environment. The proposed method for transmission expansion planning takes into account a number of potential scenarios on the basis of an annum and is solved by a mixed-integer non-linear programming method as well as by a proposed iterative two-stage approach. The effectiveness of proposed approach is tested on Garver's 6-bus, the IEEE 24-bus reliability test, the IEEE 57-bus, and the IEEE 118-bus systems. The comparisons of the proposed approach are presented (a) without including reactive power procurem cost in the present formulation and (b) with an existing DC formulation based transmission expansion planning approach.